Impact of Internet Marketing Capabilities, Orientations, Uncertainty, and Innovation on International Performance - Fendy Cuandra; Viviana Angesty; Edy Yulianto Putra; Lady Lady (JBTI : Jurnal Bisnis : Teori dan Implementasi, 2025)
SMEs play a critical role in driving economic development through international expansion in the globalization era. However, understanding which strategic capabilities truly enhance their global performance remains a challenge. This paper examines different factors that influence international performance, with a focus on innovation as a mediating factor. This research utilized a quantitative method and a purposive sampling approach. The data were analyzed by using SPSS and Smart PLS 3.0. The sample was 204 international SMEs from Indonesia. The result found that internet marketing capabilities, learning orientation, entrepreneurial orientation, and market orientation influence the international performance of SMEs. Nevertheless, uncertainty and innovation do not significantly affect the international performance of SMEs, nor does innovation mediate the relationship between market orientation and international performance. The international environment typically requires firms to understand customers' needs and perceive themselves as capable of understanding their competitors. Also, sharing insight with suppliers and other stakeholders helps companies recognize valuable partnerships and enhance their international performance. This study contributes to the understanding of how strategic orientations and internet marketing capabilities drive international SME performance. It challenges the assumption that innovation and uncertainty significantly impact global market success, highlighting instead that SMEs benefit more from market orientation, learning orientation, and digital marketing capabilities in achieving international growth.